Literature Review: The Effect of Online Shops on Consumer Shopping Satisfaction - Muhammad Ammar Muhtadi (The Eastasouth Management and Business, 2023)
Technology makes times change, this change will be followed by increasing needs and different desires in the future, especially shopping needs. Online shopping is becoming popular, especially in groups of people who usually use internet services. Online shopping activities can be done through smartphones, tablets, and laptops that are connected to the internet network. Consumer satisfaction is also one of the most important factors in doing business online to be able to win the competition. The purpose of this study is to determine the effect of online shopping on consumer shopping satisfaction accompanied by the factors that make online shopping able to provide satisfaction for consumers. The method used in this research is the literature review method. That is a literature search conducted through Google Scholar. In the early stages of the article search, 52,200 scientific articles were obtained using the keywords "online shop, consumer satisfaction". From the many findings after being selected based on the criteria, only 5 journals were included in this study. The results of this study also show that the influence of the online shop on consumer shopping satisfaction greatly determines the development of the online shop. Shopping that becomes easy and practical does not need to spend a lot of time and energy, making consumers choose to shop online and related to the satisfaction felt by consumers, which can be seen from various things, one of which is according to the needs and tastes they want.